Research on stress release for the gob-side roadway using the roof-cutting technology with a chainsaw arm - Yang Tai; Bin Yu; Binwei Xia; Zhao Li; Hongchu Xia (Royal Society Open Science, 2020)
The narrow pillar mining method is widely adopted for working faces in coal mines. However, in cases of an overlying hard roof, a suspended triangle roof plate or a cantilever will be formed near the goaf. At this point, the coal pillar extrusion and serious deformation will occur in the gob-side roadway. In order to mitigate the problem, the roof-cutting technology with a chainsaw arm and its equipment have been developed. In this paper, based on the analysis of deformation and failure characteristics of 2312 roadway, which is close to the goaf of 2311 working face in Tashan Coal, the roof-cutting technology with a chainsaw arm was chosen to be applied in 2311 roadway. Then, the roof-cutting process and the load acting on the coal pillar were discussed and analysed. A numerical model was established to analyse the stress releasing effects after roof cutting. Moreover, the roof-cutting height and the support parameters of the roadway were optimized through numerical analysis and the results manifested that the roof cutting was the most effective when the roof-cutting height was 6.4 m. After roof cutting, the vertical stresses within the coal pillars were lowered by about 25.0%. Finally, the roof-cutting experiment was carried out in the 2311 roadway in Tashan Coal Mine. The on-site roof-cutting depth was 6.4 m and the roof-cutting width was 42 mm guided by the numerical analysis. To verify the stress-relieving effects, the borehole stress meters were applied to monitor the peak advancing stresses of narrow pillars at various depths. The measured results indicated that the peak advancing stresses decreased by 22.8% on average, and therefore, roof cutting and stress releasing effects were achieved.